Case report: Partial cystectomy for pheochromocytoma of the urinary bladder: A case report and review of literature - Hu, Liang-Liang; Guo, Zhong-Qiang; Dai, Peng; Chen, Gang; Tian, Tao (Frontiers in Cardiovascular Medicine, 2022)
Pheochromocytomas are neuroendocrine tumours that produce catecholamines and can be difficult to diagnose. Bladder involvement is uncommon with pheochromocytoma. Hypertension (sometimes with hypertensive crisis coinciding with micturition), headache, hematuria and syncope, which are commonly associated with voiding, are the most prevalent symptoms. While transurethral resection may be performed in roughly 20% of patients, 70% require partial cystectomy and 10% require radical cystectomy. We present a case of pheochromocytoma with hypertension and syncope that was often associated with voiding, satisfactorily treated by partial cystectomy.